Citizen attitudes toward errors in criminal justice: implications of the declining acceptance of Blackstone's ratio - Xiong, Moulin (International journal of law, crime and justice, 2017)
The “Blackstone ratio,” positing that “it is better that ten guilty individuals escape, than that one innocent suffer,” is a well-known principle of criminal justice. The methods of implementing the legal policy of maximum possible certainty of guilt congruent with Blackstone's ratio consists of a constellation of constitutional and statutory rights, as well as rules of procedure and evidence. However, what if the public shifts its view of the Blackstone's ratio and becomes less supportive of this principle? This paper reports the results of a cross-national study of public opinion regarding whether it is worse to wrongfully convict the innocent, or erroneously acquit the guilty. Reanalysis of the results of four different surveys of citizens in different countries conducted from 1985 to 2006 reflects a significant and growing rejection of the Blackstone ratio principle over the time period studied. We discuss one implication of these findings relating to the standard of proof in criminal cases, and suggest directions for future research.